Measurements and movements of Madagascar Teal Anas bernieri captured and ringed at Lake Antsamaka in central-western Madagascar - Razafindrajao, Félix; Young, H Glyn; bin Aboudou, Abdallah Iahia (Wildfowl, 2012)
Madagascar Teal Anas bernieri were captured at Lake Antsamaka, central-western Madagascar, during the species’ annual wing moult to test whether the sexes could be differentiated on morphometrics and report on a little-known species. A total of 345 birds were caught, measured and ringed over a 13 year period (1997–2009), of which 73 were recaptured. Males and females did not differ significantly in body mass; for other body measurements (tarsus, culmen and skull) males were significantly larger. Body mass did not change significantly with wing length for moulting birds re-growing their feathers, implying an adequate food supply to maintain mass during moult at the site. Wing length increased linearly at a rate of 5.72 mm/day in individuals recaptured 1–8 days after first being caught, indicative of feather growth over this period, with growth rates stabilising and diminishing thereafter. One adult female (aged at least 2 years) was caught eight years after first capture, indicating that Madagascar Teal can reach an age of at least 10 years in the wild. Individuals caught and ringed during moult moved up to c. 200 km from the ringing site. Declines in numbers moulting at Lake Antsamaka during our study were linked to water depth at the site, which is in turn apparently linked to annual precipitation. Conservation of this species requires protection of the population in several watersheds and at moulting sites where it is very vulnerable to disturbance, capture for food by local people and predation.